2007
DOI: 10.1007/s10295-007-0214-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of phenotypic and genetic characteristics between two desulfurizing isolates of Rhodococcus erythropolis and the well-characterized R. erythropolis strain IGTS8

Abstract: Two Rhodococcus erythropolis isolates, named A66 and A69, together with the well-characterized R. erythropolis strain IGTS8 were compared biochemically and genetically. Both isolates, like strain IGTS8, desulfurized DBT to 2-hydroxybiphenyl (2-HBP), following the 4S pathway of desulfurization. Strain IGTS8 showed the highest (81.5%) desulfurization activity in a medium containing DBT at 30 degrees C. Strain A66 showed approximately the same desulfurization activity either when incubated at 30 degrees C or at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…), R. erythropolis isolates A66 and A69 (Santos et al . ) and G. alkanivorans RIPI90A (Shavandi et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…), R. erythropolis isolates A66 and A69 (Santos et al . ) and G. alkanivorans RIPI90A (Shavandi et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…This technique considers phenotypic, genotypic and molecular characteristics of microorganisms. Santos et al (2007) started this polyphasic approach with two isolates of R. erythropolis. The authors showed that both isolates involved in the ''4S'' pathway, reached desulfurization rate of 81.5 %, indicating that the isolates meet the necessary requirements for biorefining fuels.…”
Section: Biodesulfurization Currentlymentioning
confidence: 99%
“…Members of the Rhodococcus genus have been intensively studied owing to their ability to survive under extreme conditions (3, 4), and these bacteria seem to be interesting targets for screening radiation-resistant genes (5). Furthermore, although many investigations have demonstrated the resistance of Rhodococcus bacteria to UVC exposure, there is a lack of information on their resistance to gamma radiation.…”
Section: Genome Announcementmentioning
confidence: 99%